North American Unconventional Gas Conference and Exhibition 2011
DOI: 10.2118/144093-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Propane (LPG) Based Hydraulic Fracturing In The McCully Gas Field, New Brunswick, Canada

Abstract: New Brunswick Canada's first commercial unconventional gas field, the McCully field, is located near the town of Sussex in southern New Brunswick. The field is comprised of low permeability Hiram Brook sandstones as well as the underlying Frederick Brook shale. The McCully field started producing gas from the Hiram Brook in April 2003 from two wells and was followed by full production in June 2007. Currently there are twenty-nine wells producing from the Hiram Brook. The Frederick Brook shale wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Carbon dioxide (widely available, cleans up formations well but lacks an economic viscosifier) (Enick, 2012). Liquid propane/butane (LPG) is widely available, has a number of cost effective viscosifiers but handling a flammable LPG is a challenge (LeBlanc, 2011;Tudor, 2009). Both have been used to limited extents but both have extensive logistical challenges with fluid supply and onsite storage at the volumes and rates of today's multi-stage hydraulic fracturing operations applied to source rocks.…”
Section: Source Rocks and Frackingmentioning
confidence: 99%
“…Carbon dioxide (widely available, cleans up formations well but lacks an economic viscosifier) (Enick, 2012). Liquid propane/butane (LPG) is widely available, has a number of cost effective viscosifiers but handling a flammable LPG is a challenge (LeBlanc, 2011;Tudor, 2009). Both have been used to limited extents but both have extensive logistical challenges with fluid supply and onsite storage at the volumes and rates of today's multi-stage hydraulic fracturing operations applied to source rocks.…”
Section: Source Rocks and Frackingmentioning
confidence: 99%
“…On the other hand, because LPG is miscible in gas and liquid hydrocarbons, little or no fracture-face damage is expected from use of gelled LPG fracturing fluid. LeBlanc et al (2011) reported that production results were approximately doubled with gelled LPG. For our example assessment, we assumed that no fracture-face damage would occur during use of gelled LPG fluid.…”
Section: Example Qfmsmentioning
confidence: 99%
“…The mentioned strategy has achieved great success, but has also met some limitations in field application. Fracturing with water‐based working fluid would consume a huge amount of water and induce potential damages to both the formation and the environment; hence, scholars have been trying to introduce non‐aqueous fracturing fluids (including carbon dioxide, liquefied petroleum gas, and nitrogen) recently. Due to low viscosity, carbon dioxide used as fracturing fluid would benefit induction of complex fractures in stimulated reservoirs.…”
Section: Introductionmentioning
confidence: 99%